2022
DOI: 10.4330/wjc.v14.i7.438
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with reduced, mildly reduced, or preserved left ventricular ejection fraction: Has reasoning been lost?

Abstract: Left ventricular (LV) ejection fraction (LVEF), defined as LV stroke volume divided by end-diastolic volume, has been systematically used for the diagnosis, classification, and management of heart failure (HF) over the last three decades. HF is classified as HF with reduced LVEF, HF with midrange or mildly reduced LVEF, and HF with preserved LVEF using arbitrary, continuously changing LVEF cutoffs. A prerequisite for using this LVEF-based terminology is knowledge of the LVEF normal range, which is lacking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The pressure on the oesophagus causes cardiac dysphagia, and when it affects the left recurrent laryngeal nerve causing palsy is called Ortner's syndrome 4,5 . HF is universally classified into three categories: HF with reduced left ventricular ejection fraction (HFrEF), HF with mildly reduced LVEF, and HF with preserved LVEF (HFpEF) 6,7 . HFpEF is a heterogeneous group of patients with symptoms of HF having preserved LVEF ≥50%, presenting with comorbidities like hypertension, diabetes, obesity, coronary artery disease, chronic kidney disease, atrial fibrillation, anemia, and other specific causes such as cardiac amyloidosis 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure on the oesophagus causes cardiac dysphagia, and when it affects the left recurrent laryngeal nerve causing palsy is called Ortner's syndrome 4,5 . HF is universally classified into three categories: HF with reduced left ventricular ejection fraction (HFrEF), HF with mildly reduced LVEF, and HF with preserved LVEF (HFpEF) 6,7 . HFpEF is a heterogeneous group of patients with symptoms of HF having preserved LVEF ≥50%, presenting with comorbidities like hypertension, diabetes, obesity, coronary artery disease, chronic kidney disease, atrial fibrillation, anemia, and other specific causes such as cardiac amyloidosis 8 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 HF is universally classified into three categories: HF with reduced left ventricular ejection fraction (HFrEF), HF with mildly reduced LVEF, and HF with preserved LVEF (HFpEF). 6,7 HFpEF is a heterogeneous group of patients with symptoms of HF having preserved LVEF ≥50%, presenting with comorbidities like hypertension, diabetes, obesity, coronary artery disease, chronic kidney disease, atrial fibrillation, anemia, and other specific causes such as cardiac amyloidosis. 8 Lately, many studies focus on identifying the clear-cut between the phenogroups of patients with HFpEF, to find those who would have the potential to benefit from targeted interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure with preserved ejection fraction (HFpEF) [heart failure (HF) with preserved left ventricular ejection fraction (LVEF)] has been defined as HF in the presence of LVEF usually > 40%-55%. However, this HF type raises serious confusion resulting from the arbitrary nomenclature, the presumed underlying pathophysiology, and the supposed features, all of which dramatically impact patient management[ 1 ]. The nomenclature HFpEF is inappropriate as several recent studies have shown that the hazard ratios for mortality during follow-up have a U-shaped relationship for echocardiographically determined LVEF with a nadir of risk at a LVEF of 60%–65% regardless of the presence or absence of HF[ 2 ].…”
Section: To the Editormentioning
confidence: 99%
“…According to the traditional view, HF is categorized based on the left ventricular ejection fraction (LVEF) in HF with reduced (HFrEF; LVEF < 40%), mid-range (HFmrEF; LVEF 40–49%), or preserved ejection fraction (HFpEF; LVEF ≥ 50%). Nevertheless, LVEF categorization has several limitations (i.e., imprecise physiological implications, substantial intra- and inter-observer variability between LVEF measurements, arbitrary LVEF cut-offs, LVEF transitions) and has been challenged (i.e., epidemiological, clinical, pathophysiological, and therapeutic features are common across the HF spectrum) [ 2 , 3 , 4 , 5 , 6 ]. In this regard, the neurohormonal overactivity syndrome (NHOS), which is present in all symptomatic HF patients, irrespective of the LVEF, contributes to the development of signs and symptoms (please see Pathophysiology section), is a major determinant of outcomes [ 7 , 8 ] ( Figure 1 ) and is the only currently available treatment target to reduce rehospitalizations and prolong survival [ 5 ].…”
Section: Introductionmentioning
confidence: 99%